SPE Annual Technical Conference and Exhibition 2019
DOI: 10.2118/195893-ms
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Heel Dominant Liquid Loading in Unconventional Horizontal Wells

Abstract: As a common occurrence in production operations, liquid-rich horizontal gas (and gassy oil) wells in unconventional plays develop severe instabilities at different stages of their well life. In this novel work, we first quantify the three-phase gas-oil-water multiphase flow behavior leading up to the characteristic severe loading signatures in order to better understand the dynamic heel-dominant liquids loading. Then, we demonstrate how a simple analytical diameter-and-inclination-dependent critical gas veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Slugging is an undesired phenomenon creating flow instabilities, which can impair the performance of liquid-producing wells, as shown in [1,5,6], which also has implications for gas-well liquid-loading studies, as shown in [7][8][9][10][11][12][13][14], and CO 2 storage due to wellbore phase change, as shown in [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Slugging is an undesired phenomenon creating flow instabilities, which can impair the performance of liquid-producing wells, as shown in [1,5,6], which also has implications for gas-well liquid-loading studies, as shown in [7][8][9][10][11][12][13][14], and CO 2 storage due to wellbore phase change, as shown in [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%